Pengaruh Aplikasi Gel Ekstrak Apel (Malus Domestica) Terhadap Kelarutan Kalsium Gigi - Delyana Fitria Dewi; Martha Mozartha; Rini Bikarindrasari (Denta Journal Kedokteran Gigi, 2019)
Background: Tooth discoloration is a common problem in dentistry. One of non-invasive treatment is tooth whitening using 10% carbamide peroxide, however these materials had been reported to cause negative impacts on the tooth. Apples are natural sources that have potential to be used as tooth whitening agent. Objective: to determine the effect of apple gel extract (Malus domestica) as an alternative material of home bleaching on dental calcium solubility. Methods: Thirty two premolar teeth were each sectioned into 2 parts and mounted on wax, and divided into 4 groups. The lingual part of the tooth was used to measure the calcium content (pretest) using atomic absorption spectrophotometry, then the bleaching procedure was done on the buccal part of the tooth. Ten percent of carbamide peroxide was applied to group A (control). Apple gel extract (AGE) was made by soxhletation method and used as treatment group. AGE 25%, 50%, and 75% was applied to group B, C, and D respectively. Afterwards all specimens were immersed in distilled water. The calcium content was measured (post test) after 14 days interval. Result: The differences between pre and post-test of calcium solubility for group A (0,37±0,10); B (0,20±0,07); C (0,28±0,06); and D (0,33±0,05). The result of statistical test showed that there were significant differences between the control group and the treatment group that was group B. Conclusion: The application of apple gel extract as an alternative material of home bleaching can dissolve tooth calcium.